Evaluation of GVPC and BCYE Media for Legionella Detection and Enumeration in Water Samples by ISO 11731: Does Plating on BCYE Medium Really Improve Yield? - Scaturro, Maria (Pathogens, 2020)
Legionella spp are the causative agents of Legionnaires’ diseases, which is a pneumonia of important public health concern. Ubiquitous freshwater and soil inhabitants can reach man-made water systems and cause illness. Legionella enumeration and quantification in water systems is crucial for risk assessment and culture examination is the gold standard method. In this study, Legionella recovery from potable water samples, at presumably a low concentration of interfering microorganisms, was compared by plating on buffered charcoal yeast extract (BCYE) and glycine, vancomycin, polymyxin B, cycloheximide (GVPC) Legionella agar media, according to the International Standard Organization (ISO) 11731: 2017. Overall, 556 potable water samples were analyzed and 151 (27.1%) were positive for Legionella. Legionella grew on both BCYE and GVPC agar plates in 85/151 (56.3%) water samples, in 65/151 (43%) on only GVPC agar plates, and in 1/151 (0.7%) on only BCYE agar plates. In addition, GVPC medium identified Legionella species other than pneumophila in six more samples as compared with the culture on BCYE. Although the medians of colony forming units per liter (CFU/L) detected on the BCYE and GVPC agar plates were 2500 and 1350, respectively (p-value < 0.0001), the difference did not exceed one logarithm, and therefore is not relevant for Legionella risk assessment. These results make questionable the need to utilize BCYE agar plates to analyze potable water samples.